Effect of Customer Relationship Management and Product Innovation of Loyalty and Satisfaction of Bank Jawa Barat (BJB) Precious Customers - R.Rista Nurshinta Dewi; Bambang Sudaryana (Universitas Djuanda, 2020)
One strategy to succeed in competition in a turbulent business environment requires a market-oriented marketing strategy that can anticipate customer desires. This research was conducted with the aim to obtain evidence or facts empirically that explain the direct influence of the independent variable Effect of Relationship Management and Product Innovation on customer loyalty and satisfaction of Precious BJB Customers. The research method used in this study is a quantitative method. Data analysis was performed using multiple linear regression. The population in this study was 533 members / BJB precious customers. The sample in this study using the Slovin formula amounted to 290 people. The results showed that the variable Influence of Relationship Management and Product Innovation had a positive effect on the Loyalty and Customer Satisfaction of BJB Precious.